Pharmacological activation of pyruvate kinase M2 reprograms glycolysis leading to TXNIP depletion and AMPK activation in breast cancer cells - Almouhanna, Fadi; Blagojević, Biljana; Can, Suzan; Ghanem, Ali; Wölfl, Stefan (Cancer & metabolism, 2021)
Aerobic glycolysis, discovered by Otto Warburg, is a hallmark of cancer metabolism even though not yet fully understood. The low activity of the cancerous pyruvate kinase isozyme (M2) is thought to play an important role by facilitating the conversion of glycolytic intermediates to other anabolic pathways to support tumors’ high proliferation rate.
Gesehen am 23.02.2021